PHYSICO-MECHANICAL PROPERTIES OF ELASTOMERS BASED ON NATURAL RUBBER FILLED WITH SILICA AND CLAY - OGBEMUDIA JOSEPH OGBEBOR; UZOMA NDUBUISI OKWU; FELIX EBHODAGHE OKIEIMEN; DANIEL OKUONGHAE (Chemical Industry and Chemical Engineering Quarterly, 2010)
Elastomers based on natural rubber (NR) and silica and clay fillers have been investigated for their physico-mechanical properties. The various mixes were compounded in a Banbury-Pullen laboratory mill and vulcanized using the efficient vulcanization system. The oscillating disc rheometer (ODR) was used for determination of cure characteristics. It was estimated that replacement of silica with clay up to 30 phr (50% replacement) increased the compound cure rate with a reduction in absolute torque level (Tmax) of the natural rubber mix. Scorch time (Ts2) was observed to be the highest at a 30/30 filler ratio. Hardness and tensile properties of obtained elastomeric materials were studied. The results show a decrease in parameters as the replacement of silica with natural clay progresses. There was improvement in elongation at break with the increase of clay content. The replacement of silica filler with clay reduced the abrasion properties (mg loss/1000 rev.)